Habitat complexity and community composition: Relationships between different ecosystem engineers and the associated macroinvertebrate assemblages - Sueiro, M.C. (2011)
Several species of ecosystem engineers inhabiting coastal environments have been reported structuring different kinds of communities. The magnitude of this influence often depends on the habitat complexity introduced by the engineers. It is commonly accepted that an increase in habitat complexity will result in an increase in diversity and/or abundance in the associated fauna. The rocky salt marshes along the coast of Patagonia are dominated by cordgrasses, mussels, and barnacles forming a mosaic of engineered habitats with different complexity. This system allows us to address the following questions: how different is a macroinvertebrate assemblage when dominated by different ecosystem engineers? And, is there a positive relationship between increasing habitat complexity and the species richness, diversity and total density of the assemblages? To address these questions, we compared the three ecological scenarios with decreasing habitat complexity: cordgrass-mussel, mussel, and barnacle-engineered habitats. We found a total of 22 taxa mostly crustaceans and polychaetes common to all scenarios. The three engineered habitats showed different macroinvertebrate assemblages, mainly due to differences in individual abundances of some taxa. The cryptogenic amphipod Orchestia gammarella was found strictly associated with the cordgrass-mussel habitat. Species richness and diversity were positively related with habitat complexity while total density showed the opposite trend. Our study suggests that species vary their relative distribution and abundances in response to different habitat complexity. Nevertheless, the direction (i. e., neutral, positive or negative) and intensity of the community's response seem to depend on the physiological requirements of the different species and their efficiency to readjust their local spatial distribution in the short term. © 2010 Springer-Verlag and AWI.